Treatment-emergent central sleep apnea associated with non-positive airway pressure therapies in obstructive sleep apnea patients: A systematic review. (August 2021) - Berger, Mathieu; Solelhac, Geoffroy; Horvath, Christian; Heinzer, Raphael; Brill, Anne-Kathrin
Summary: This systematic review summarizes the prevalence of treatment-emergent central sleep apnea (TECSA) occurring with therapies other than positive airway pressure (PAP) for the management of obstructive sleep apnea (OSA). We describe its natural course as well as the proposed underlying pathophysiological mechanisms and the clinical management of affected patients. A systematic search of PubMed, Embase, Web of science, and the Cochrane Library was performed until June 2020. Eighteen studies (n = 284 patients) were included. TECSA was observed in 31 patients with the use of four different medical devices (mandibular advancement device, hypoglossal nerve stimulation, tongue stabilizing device and nasal expiratory PAP) and after three different types of surgical treatments (tracheostomy, maxillofacial surgery and oro-nasal surgery). Due to the paucity of data available, it was not possible to establish a clear prevalence rate of TECSA for each alternative treatment. After the initiation of non-PAP treatments, a systematic reassessment of the treatment efficacy with follow-up sleep studies will be helpful to identify TECSA. A spontaneous resolution over time was described as well as a persistence of TECSA. In this case, treatment should focus on patients' specific underlying pathophysiology. Overall, the limited current literature suggests that this phenomenon is rare (<4%).